Fruit softening: demonstration of in-vivo pectate lyase and rhamnogalacturonan lyase action - Al Hinai, Thurayya Zahran Sulaiman (The University of Edinburgh, 2022)
The programmed softening that occurs during fruit development requires scission of wall and/or middle lamella polysaccharides, especially pectin. Proposed mechanisms include the action of cell-wall enzymes [e.g. pectate lyase (PL), endo-polygalacturonase (EPG) or rhamnogalacturonan-I lyase (RGL)] or hydroxyl radicals ( •OH). Sometimes PL, EPG, RGL and •OH may all occur simultaneously, and it may be difficult to distinguish which play(s) the predominant role in vivo. Recent evidence has highlighted a role for PL and RGL gene expression in softening. In addition, PL and RGL activities have been reported in certain fruit extracts when assayed in vitro. However, no evidence had demonstrated the in-vivo action of PL or RGL. This project focused on finding evidence for PL and RGL in-vivo action in several softening fruits at three ripening stages (unripe, turning and ripe) by detecting their diagnostic reaction-products (‘fingerprints’) during fruit development. PL cleaves the non-methylesterified homogalacturonan domains of pectin by an elimination reaction, leaving a 4-deoxy-β-L-threo-hex-4-enopyranuronose residue (∆UA) residue as the newly formed non-reducing end. This product distinguishes PL action from EPG action, which generates a simple galacturonic acid (GalA) residue as the new non-reducing terminus. RGL cleaves the α-(1,4) glycosidic bond between rhamnose and galacturonic acid of the RG-I backbone by β-elimination, producing a new rhamnose reducing end and ΔUA as the new non-reducing end. To detect the ∆UA termini (in both PL and RGL products) in cell walls of softening fruits, cell walls (in the form of alcohol-insoluble residue; AIR) were digested with Driselase to release the smallest possible products, which were then resolved by high-voltage paper electrophoresis to reveal any products with a ∆UA residue (very low pKa) and then by thin-layer chromatography to resolve PL from RGL products. In addition to large amounts of free Driselase-generated GalA, which quantified the total pectin, appreciable amounts of both PL (∆UA–GalA) and RGL (vUA–Rha-GalA-Rha) fingerprints were detected in almost all the tested fruits including date, strawberry and mango at the three ripening stages. The ∆UA–GalA:GalA ratio from ripe date AIR was ~1:20, mol/mol, indicating approximately one PL-cleaving event per 20 GalA units of homogalacturonan. This is the first biochemical evidence of PL and RGL being in action in healthy fruits. The methodology clearly distinguishes the PL product from the RGL product and in future can be used to investigate other plant tissues as well.
Keywords: pectate lyase; rhamnogalacturonan lyase; fruit softening